2002
DOI: 10.1089/107999002320271413
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression Analysis of the Human Interferon-Inducible Gene IFI16, a Member of the HIN200 Family, Not Restricted to Hematopoietic Cells

Abstract: This is the first description of an extensive immunohistochemical analysis of interferon (IFN)-inducible gene IFI16 expression in normal tissues. Immunohistochemical detection of IFI16 in paraffin-embedded tissues is achieved by using a polyclonal antibody raised against its C-terminal fragment that recognizes its three closely migrating isoforms in Western blotting. The results clearly indicate that IFI16 expression is not restricted to the hematopoietic compartment. In normal adult human tissues, it is promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 23 publications
6
79
0
4
Order By: Relevance
“…Recent immunohistochemical analyses of IFI 16 protein in normal human tissues revealed that its expression is not restricted to hematopoietic cells (Gariglio et al, 2002;Wei et al, 2003). Additionally, hybridization of IFI 16 cDNA probe to a multiple tissue Northern blot revealed that IFI 16 mRNA expression is relatively high in several human tissues, including the prostate (Wei et al, 2003).…”
Section: Expression Of Ifi 16 Is Detectable In Normal Human Prostatementioning
confidence: 99%
See 1 more Smart Citation
“…Recent immunohistochemical analyses of IFI 16 protein in normal human tissues revealed that its expression is not restricted to hematopoietic cells (Gariglio et al, 2002;Wei et al, 2003). Additionally, hybridization of IFI 16 cDNA probe to a multiple tissue Northern blot revealed that IFI 16 mRNA expression is relatively high in several human tissues, including the prostate (Wei et al, 2003).…”
Section: Expression Of Ifi 16 Is Detectable In Normal Human Prostatementioning
confidence: 99%
“…The protein IFI 16 is primarily nuclear in lymphoid cells (Dawson and Trapani, 1995). Importantly, recent analyses of IFI 16 expression in several human tissues by immunohistochemistry revealed that expression of IFI 16 is not restricted to cells of hematopoietic origin (Gariglio et al, 2002;Wei et al, 2003). Of note, IFN induction of IFI 16 in hematopoietic cells appears to be cell-type-and donor-specific (Schlaak et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical analysis demonstrated that IFI16 is highly expressed in endothelial cells, suggesting that it may be involved in angiogenesis [28,29]. When HUVEC are maintained at subconfluent density in complete medium, they proliferate and are highly sensitive to growth arrest by contact inhibition.…”
Section: Modulation Of Ifi16 Expression During Endothelial Cell Growthmentioning
confidence: 99%
“…By contrast, only some resident macrophages were stained and granulocytes were negative. In addition, in normal adult human tissues, IFI16 is expressed in a highly restricted pattern in selected cells within certain organs [28,29]. Prominent IFI16 expression is seen in stratified squamous epithelia, particularly intense in basal cells in the proliferating compartments, whereas it gradually decreases in the more differentiated suprabasal compartment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to partially conserved repeat motifs of 200 amino acids, designated A, B and C, the IFI16 protein contains a DAPIN/PYRIN domain within its N-terminus [6,7]. This domain was identified as a putative protein-protein interaction domain at the N-terminus of several other proteins believed to function in inflammatory signalling pathways.…”
Section: Introductionmentioning
confidence: 99%